2022
DOI: 10.1021/acs.molpharmaceut.2c00244
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Lipid Nanoparticles for Protein Kinase N3 shRNA Delivery and Prostate Cancer Therapy

Abstract: Protein kinase N3 (PKN3), by virtue of its abnormal expression in prostate cells, has been widely used as a target of RNAi (shRNA, siRNA, miRNA) therapy. The major challenges of PKN3 RNAi therapy lie in how to design effective interference sequences and delivery systems. Herein, new PKN3 shRNA sequences (shPKN3-2459 and shPKN3-3357) were designed, and bioreducible, biodegradable, ionizable lipid-based nanoparticles were developed for shPKN3 delivery. First, an ionizable lipid (DDA-SS-DMA) bridged with disulfid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Wang et al designed ionizable liposomes to carry protein kinase N3 (PKN3), which is aberrantly expressed in prostate cancer cells. The nanoparticles vigorously suppressed tumor growth (65.8%) and improved therapeutic safety [ 116 ]. Similarly, nanoparticles containing PTT/PDT have been used in prostate cancer.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Wang et al designed ionizable liposomes to carry protein kinase N3 (PKN3), which is aberrantly expressed in prostate cancer cells. The nanoparticles vigorously suppressed tumor growth (65.8%) and improved therapeutic safety [ 116 ]. Similarly, nanoparticles containing PTT/PDT have been used in prostate cancer.…”
Section: Prostate Cancermentioning
confidence: 99%
“… 103 Wang and colleagues silenced protein kinase N3 (PKN3), strongly expressed in prostate cancer cells, by developing a bioreducible, biodegradable, and ionizable lipid-based NP encapsulating shPKN3. 104 This innovative method counteracted cancer progression and was a more effective and less toxic transfectant agent increasing in vivo tumor suppression. 104 Recent evidence showed the antitumor action of icaritin loading poly (lactic-co-glycolic acid) (PLGA@Icaritin) NPs in in vivo models of gastric cancer.…”
Section: Nps For Cancer Treatmentmentioning
confidence: 99%
“… 104 This innovative method counteracted cancer progression and was a more effective and less toxic transfectant agent increasing in vivo tumor suppression. 104 Recent evidence showed the antitumor action of icaritin loading poly (lactic-co-glycolic acid) (PLGA@Icaritin) NPs in in vivo models of gastric cancer. Particularly, PLGA@Icaritin NPs stimulated ROS production, altered mitochondrial membrane potential lowering, and enhanced immune system response against tumor cells, thus impairing cancer progression.…”
Section: Nps For Cancer Treatmentmentioning
confidence: 99%
“…The creation of obstructing sequences and delivery mechanisms is a significant current problem in PKN3 RNAi treatment. Wang et al [ 174 ] synthesized a multifunctional ILNP (DDA-SS-DMA) that integrated ester bonds and disulfide bonds for PKN3 shRNA delivery and prostate cancer therapy. In particular, shPKN3-3357 and shPKN3-2459 were also developed as novel PKN3 shRNA sequences.…”
Section: Applications Of Iddss In the Treatment Of The Diseasesmentioning
confidence: 99%
“…The results showed that ILNP containing the ionizable cationic lipid (DLin-KC2-DMA) effectively silenced the AR gene in both wild-type AR-expressing cells (LAPC-4) and LNCaP xenograft tumors. This study also suggested that strategies to improve targeting of ILNP AR-siRNA systems to prostate cancer cells may be more effective in knocking down AR and treating advanced prostate cancer [ 174 , 175 ].…”
Section: Applications Of Iddss In the Treatment Of The Diseasesmentioning
confidence: 99%